Evaluation as key to describing the enacted object of learning. Issue 3 (13th July 2015) - Ulla Runesson, Professor; Pillay, Vasen; Adler, Jill
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to illustrate the methodology used by the authors to describe the enacted object of learning, a methodology where data production and analysis is rooted in a theorisation of pedagogy. The authors share how the authors used this methodological approach to provide a comprehensive description of the enacted object of learning and in so doing the authors hope to make a methodological contribution to the field of learning study. The lesson analysis foregrounds the importance of "evaluation" in pedagogic practice, and thus a key element of pedagogy. Tools from variation theory are incorporated into this broader approach that the authors suggest illuminates the enacted object of learning. The authors offer this approach as a methodological contribution to the development of research in and on learning study. Design/methodology/approach – A case study approach was adopted as the key research methodology in this study. The four teachers who participated in this study were purposively identified since in the first instance the design of the study warranted that the teachers who participated were teaching mathematics at grade 10. Second, the need to be purposive in the sampling strategy employed was based on issues around cost, logistics and convenience. Findings – While learning study foregrounds the importance of examining the constitution of the enacted object of learning, the contention is that it is through a focus on evaluation that the authors are able to fully describe what is constituted as mathematics with respect to the enacted object of learning. Analysis of evaluation thus adds to the description of the enacted object in critical ways. Originality/value – Within the domain of learning study, this paper provides a novel way of engaging with a lesson transcript in an attempt to fully describe what comes to be constituted as the enacted object of learning. This is achieved by combining the notion of evaluative events and authorisation on one hand and variation theory on the other.